The Characteristics of Anxious Students in Speaking Class - Widia Kusuma Wardani (Universitas Muhammadiyah Yogyakarta, 2018)
This research investigates the characteristics of anxious students in speaking class. This was conducted in a private university in Yogyakarta. Two instruments were used in this study, which were structured observation and standardized open-ended interview. Two classes were observed. From the observation, six students were chosen to become the participants. There were twenty characteristics found in this study which finally divided into observable symptoms and non-observable symptoms. The symptoms which included in observable symptoms were trembling, avoiding eye contact, squirming, playing with hair or clothing, nervously touching object, stuttering or stammering, getting sweaty, rubbing the palms, staggering voice, reading from the script while giving presentation, speaking too fast, speaking too slow, remaining silent, using filler, having pale face, and having poor stance. While the non-observable symptoms were getting confused, getting cold, feeling nervous, and heart beating quickly.